Lhowa Phonology: A Typological Perspective - Regmi, Dan Raj; Regmi, Ambika (Gipan, 2024)
Lhowa exhibits a large inventory of forty-one consonant phonemes. In terms of points of articulation, it contains seven types of consonants, viz., labial, dental, alveolar, retroflex, palatal, velar and glottal. In terms of manner of articulation, it presents seven types of consonants, viz., stops, nasals, affricates, fricatives, trills, laterals and approximants. In terms of voicing, there are two types of consonant phonemes, viz., voiceless and voiced. Lhowa has voiceless unaspirated, voiceless aspirated, voiced murmured and voiceless murmured sounds. It exhibits a distinct consonant distribution. Lhowa has eight basic and two fronted vowels. There are four diphthongs. Lhowa displays a moderately complex syllable structure. It presents a canonical structure of the syllable in which V is obligatory and other constituents, (Ci, initial consonant), (X, voiced palatal approximant), and (Cf, final consonant) are optional. Lhowa permits only five types of syllable patterns. Each syllable is intrinsically high or low. It exhibits simple tone system. The high vs. low tone is distinguished only on the first syllable of a word. In Lhowa, like in Lhasa Tibetan, compound words demonstrate four types of tone melodies, viz., HH, LH, LL and HL.